Correction to: Impact of environmental cleaning on the colonization and infection rates of multidrug-resistant Acinetobacter baumannii in patients within the intensive care unit in a tertiary hospital - Yang Li (Antimicrobial Resistance and Infection Control, 2021)
An amendment to this paper has been published and can be accessed via the original article.